Impact of direct substitution of arm span length for current standing height in elderly COPD - Chaicharn Pothirat (2018)
© 2015 Pothirat et al. Background: Arm span length is related to standing height and has been studied as a substitute for current standing height for predicting lung function parameters. However, it has never been studied in elderly COPD patients. Purpose: To evaluate the accuracy of substituting arm span length for current standing height in the evaluation of pulmonary function parameters and severity classification in elderly Thai COPD patients. Materials and methods: Current standing height and arm span length were measured in COPD patients aged > 60 years. Postbronchodilator spirometric parameters, forced vital capacity (FVC), forced expiratory volume in first second (FEV 1 ), and ratio of FEV 1 /FVC (FEV 1 %), were used to classify disease severity according to global initiative for chronic obstructive lung disease criteria. Predicted values for each parameter were also calculated separately utilizing current standing height or arm span length measurements. Student’s t-tests and chi-squared tests were used to compare differences between the groups. Statistical significance was set at P < 0.05. Results: A total of 106 COPD patients with a mean age of 72.1±7.8 years, mean body mass index of 20.6±3.8 kg/m2, and mean standing height of 156.4±8.3 cm were enrolled. The mean arm span length exceeded mean standing height by 7.7±4.6 cm (164.0±9.0 vs 156.4±8.3 cm, P < 0.001), at a ratio of 1.05±0.03. Percentages of both predicted FVC and FEV 1 values based on arm span length were significantly lower than those using current standing height (76.6±25.4 vs 61.6±16.8, P < 0.001 and 50.8±25.4 vs 41.1±15.3, P < 0.001). Disease severity increased in 39.6% (42/106) of subjects using arm span length over current standing height for predicted lung function. Conclusion: Direct substitution of arm span length for current standing height in elderly Thai COPD patients should not be recommended in cases where arm span length exceeds standing height by more than 4 cm.